Lived experiences of farmworkers from five U. S. states during the COVID-19 pandemic - Herrán, Keren; Mandujano-Acevedo, Nicandro; Suarez, Jocelyn Claudel; Boggess, Bethany; Frongillo, Edward A. (Frontiers in Public Health, 2025)
ObjectiveThe nexus of farmworker and COVID-19 peer-reviewed research has yet to be advanced by qualitative analysis that: (1) focuses on multiple dimensions of farmworker’s daily life and (2) uses a geographically diverse sample. The present data collection project fills this gap by using the National Center for Farmworker Health’s (NCFH) Farmworker COVID-19 Community Assessment (FCCA) Phase 2 dataset which contains a varied sample of farmworkers and local experts across selected counties in five states. The NCFH FCCA Phase 2 data were analyzed to characterize how farmworkers from a multistate sample experienced COVID-19 impact their daily lives, with particular focus on understanding farmworker vaccine experiences, familial dynamics, and actions implemented by employers.MethodsParticipants (n = 28; farmworker n1 = 19, local expert n2 = 9) were recruited via purposive and snowball sampling. NVivo software and grounded theory coding were used for data analysis. Techniques utilized to ensure rigorous qualitative research were: (1) continuously applying researcher reflexivity, (2) purposive sampling, and (3) investigator and data triangulation.ResultsCOVID-19 primarily impacted three spheres of farmworker’s daily life: health, family, and the workplace. Of the emergent themes, novel findings include farmworkers’ motivation for vaccination, farmworkers’ anguish concerning extended family, the deterioration of unity in farmworkers’ families, and identification of what workplace changes farmworkers deemed helpful. These novel findings widen understanding of how farmworker health can be promoted in the event of another pandemic. Although present recommended strategies (e.g., improving housing conditions and disseminating health information in Spanish) are valuable in ensuring optimal well-being of farmworkers long-term, policymakers and public health professionals should also design and integrate actions that target farmworkers’ vaccine motivations, promote unity/connection within the extended and nuclear family, and incentivize employers to implement workplace changes that farmworkers value.